A narrative study of mental health recovery: exploring unique, open-ended and collective processes. Issue 1 (1st January 2020) - Reed, Nina Petersen; Josephsson, Staffan; Alsaker, Sissel
ABSTRACT: Purpose : Guided by narrative theory and by use of a narrative-in-action approach, the aim of this study was to explore how mental health recovery unfolds through individuals' engagement in everyday activities. Method : Data were created through participant observations with four individuals while doing everyday activities, and analysed through a narrative, interpretive approach. Findings : The findings show how mental health recovery involves unique and open-ended processes of narrative meaning-making, which unfold through an interplay between everyday activities, places and persons. Discussion : Based on these findings, we discuss how we may understand and support mental health recovery as collective processes.